827 Elucidating the roles of PIK3IP1/TrIP immune regulation on distinct T cell subsets in the context of cancer. (10th December 2020) - Murter, Benjamin; Kane, Lawrence
Abstract : Background: The signaling pathways involving phosphoinositide-3-kinases (PI3Ks) are highly conserved and tightly regulated to influence the activation, proliferation, and survival of all cell types. PI3K signaling plays a major role in T cell responses to antigen due to its position directly downstream of T cell receptor (TCR)/CD28 ligation. Our lab has recently shown that the cell surface protein TrIP (Transmembrane Inhibitor of PI3K, gene name: Pik3ip1) is capable of downregulating PI3K signaling in CD4+ T cells and can act as a negative regulator of T cell immune responses. 1 This negative immune regulation was just recently reported to promote anti-tumor immunity, implicating TrIP as a potential immunotherapy target. 2 Interestingly, although all effector subsets re-express TrIP to varying degrees, public expression data shows that Treg cells maintain higher TrIP message than other T-effector subsets. 3 Methods: Using a conditional TrIP knockout mouse model developed in our lab, we have begun to interrogate how TrIP expression regulates the opposing activities of CD8+ T cells vs. Treg and how these affect the overall tumor immune landscape. With Treg-specific TrIP KO, we assessed the effects on syngeneic tumor growth in vivo, as well as analyzed primary and tumor-derived Treg phenotypes ex-vivo. Results: Thus far, we have found that TrIP knockout in the Treg compartment leads to no detectable differences in tumor burden. However, the lack of TrIP expression on Treg does have some effect on the effector phenotype of Treg cells isolated from the tumor. Conclusions: We describe preliminary data on the role of TrIP in Treg function and phenotype and have begun to explore its effects on the tumor microenvironment. To build on this work we are currently developing TrIP over-expressing lentiviral constructs to compliment the knockout approaches described here. We have also now obtained mice with tamoxifen-inducible TrIP KO in Treg, so we will determine whether the timing of TrIP deletion affects the impact of TrIP deficiency. References: Uche UU, Piccirillo AR, Kataoka S, Grebinoski SJ, D'Cruz LM, Kane LP. PIK3IP1/TrIP restricts activation of T cells through inhibition of PI3K/Akt. J Exp Med 2018;215 :3165–3179. doi:10.1084/jem.20172018. Chen Y, Wang J, Wang X, Li X, Song J, Fang J, et al. Pik3ip1 Is a Negative Immune Regulator that Inhibits Antitumor T-Cell Immunity. Clin Cancer Res 2019;25 :6180–6194. doi:10.1158/1078-0432.CCR-18-4134. Heng TSP, Painter MW, Immunological Genome Project Consortium. The immunological genome project: networks of gene expression in immune cells. Nat Immunol 2008;9 :1091–1094. doi:10.1038/ni1008-1091.